Crisis and Public Support for the Euro, 1990–2014*. (8th December 2015) - Roth, Felix; Jonung, Lars; Nowak‐Lehmann D., Felicitas
Abstract: This article analyses the evolution of public support for the single European currency, the euro, from 1990 to 2014 for a 12‐country sample of the euro area (EA‐12), focusing on the most recent period of the financial and sovereign debt crisis, starting in 2008. We find that citizens' support for the euro on average was marginally reduced during the first six years of the crisis, and that support has remained at high levels. While the pronounced increase in unemployment in the EA‐12 throughout the crisis has led to a marked decline in trust in the European Central Bank (ECB), it is only weakly related to support for the euro.